Comprehensive assessment of electrospun scaffolds hemocompatibility - Horakova, Jana; Mikes, Petr; Saman, Ales; Svarcova, Tereza; Jencova, Vera; Suchy, Tomas; Heczkova, Bohdana; Jakubkova, Sarka; Jirousova, Jaroslava; Prochazkova, Renata (Materials science & engineering. C, Materials for biological applications, 2018)
Biodegradable polyesters, namely polycaprolactone (PCL) and copolymer of polylactide and polycaprolactone (PLCL) were electrospun into various fibrous structures and their hemocompatibility was evaluated in vitro. Firstly, hemolytic effect was evaluated upon incubation with diluted whole blood. The results showed that the degree of hemolysis depended on chemical composition and fibrous morphology. Electrospun polycaprolactone induced slight degree of hemolysis depending on its molecular weight and fibrous morphology; copolymer PLCL did not cause detectable hemolysis. The influence of coagulation pathways was examined by measurement of coagulation times. It was showed that intrinsic coagulation pathway assessed by activated partial thromboplastin time (APTT) was moderately accelerated after incubation with PCL and prolonged after incubation with copolymer PLCL. Extrinsic activation of coagulation tested by prothrombin time (PT) was slightly accelerated after incubation with all tested electrospun samples. Thrombogenicity assessment of fibrous samples revealed high thrombogenic properties of fibrous materials that was comparable to high degree of collagen thrombogenicity. The level of platelet activation was dependent on chemical composition and surface morphology of tested materials.
Keywords: Humans; parciální tromboplastinový čas; Polyesters; Hemolysis; Blood Cells; krevní buňky; Microscopy, Electron, Scanning; lidé; kolagen; Collagen; protrombinový čas; polymery; Biocompatible Materials; Polymers; polyestery; mikroskopie elektronová rastrovací; Partial Thromboplastin Time; Blood compatibility; Fibrous scaffolds; Copolymer of polylactide and polycaprolactone; biokompatibilní materiály; Polycaprolactone; hemolýza; Prothrombin Time